Pretesting and piloting the research instrument to examine the central roles of risk perception and attitude towards financial investment behavioral intention among Malaysians - Lim, Thien Sang; Rasid Mail; Mohd Rahimie Abd Karim; Zatul Karamah Ahmad Baharul Ulum; Mazalan Mifli; Nelson Lajuni (Penerbit UMS, 2017)
Risk perceptions and attitude are important in the context of decision-making process involving risky options because individuals normally do not have perfect information and their decision making is affected by bounded rationality. The paper aims to analyse and develop the instrument for the examination of the central roles of risk perception and attitude, sequentially, in affecting the behavioural intention towards financial investment. Items included in the pre- test and pilot test stages were adapted from literature, but not specifically related to personal finance. The two stages have significant roles in ensuring and strengthening the content validity and the reliability of the instrument. The finalised survey instrument contained a total of 40 indirect measured items, which were then employed in the study.